(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article discusses the advantages of using new pedagogical technologies in teaching Russian. In modern didactics, in many methodological works, the term pedagogical technology is encountered. In practice, there are such terms as pedagogical technologies, educational technologies, new pedagogical, innovative educational technologies. However, the concept of "technology" is still being refined, the term is used in a fairly broad context.